2017
DOI: 10.1073/pnas.1612561114
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis reveals major determinants ofcis-regulatory variation inCapsella grandiflora

Abstract: Understanding the causes of cis-regulatory variation is a long-standing aim in evolutionary biology. Although cis-regulatory variation has long been considered important for adaptation, we still have a limited understanding of the selective importance and genomic determinants of standing cis-regulatory variation. To address these questions, we studied the prevalence, genomic determinants, and selective forces shaping cis-regulatory variation in the outcrossing plant Capsella grandiflora. We first identified a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 56 publications
5
34
0
Order By: Relevance
“…Previous studies found that genes with ASE might be under relaxed purifying selection compared with genes without ASE (Josephs, Wright, Stinchcombe, & Schoen, 2017;Steige et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies found that genes with ASE might be under relaxed purifying selection compared with genes without ASE (Josephs, Wright, Stinchcombe, & Schoen, 2017;Steige et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies employing existing methods for ASE detection filter out read counts from closely spaced SNPs (Emerson et al, 2010;Steige et al, 2017). However, this reduces the amount of data available for study and limits the statistical power when testing for ASE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second study, the team was able to detect loci under ADE and selection at the same time in different human populations (Tian et al 2018). Also, approaches in a plant model, Capsella grandiflora, a species characterized by weak population structure and large effective population size, emphasized the relative impact of purifying selection and positive selection on cis-regulatory variation in populations (Josephs, Lee, Stinchcombe, & Wright, 2015;Steige, Laenen, Reimegård, Scofield, & Slotte, 2017). Our study, by focusing on whole populations of numerous individuals, offers further clues to understand the link between gene expression variation and selection.…”
Section: Population-scale Ade In O Similis Populations and Its Linmentioning
confidence: 99%
“…Thus, these sister species have become important models for understanding the morphological and genomic consequences of the progression from SI to selfing. The loss of SI is associated with differences in floral morphology [18], reproductive imprinting [19], and cis-gene regulation [20,21]. To date, these differences have been examined at the genomic level but not at the functional and genetic levels because C. grandiflora has, to our knowledge, not previously been the subject of studies that require its transformation.…”
mentioning
confidence: 99%